Adaptability of the Lean-Sigma Methodology for Operations in a Multicultural Workplace - Alba-Baena, Noé (Springer, 2021)
Overseas operations, as beneficial as there are, present challenges such as the adoption of the organizational culture, working methodologies, and practices. Different strategies have been exercised to successfully reach the expected benefits of these operations and take advantage of the local resources. Managers have faced local resistance and miscommunication barriers, moreover, the cultural differences have impacted the operations reducing in general, the efficiency of these operations. The need for integration in the cultural component has been addressed by different researchers; however, there is limited information on methodologies used for such integration. The present work proposes a methodology for the integration of the national cultural characteristics for creating a local workplace culture. The described methodology is accompanied by an example of implementation in a multicultural scenario. The case study shows the successful implementation of the Lean-Sigma methodology in response to a problematic situation in the operation site of Juarez (Mexico). A study of the local culture helps in the selection of the tools used during this implementation and to exceed the customer expectative and compete for larger projects with this and other customers.